Effect of Leaf Clipping on Yield Attributes of Modern and Local Rice Varieties (Bangladesh Rice Journal, 2018)
Impact of five different types of leaf clipping on the yield attributes of modern (Binadhan-8) and local (Terebaile) rice variety was evaluated on pot experiments following a completely randomized design (CRD) with three replications. Leaves were cut according to the treatment. Data were collected on panicle length (cm), filled grain panicle-1, unfilled grain panicle-1, thousand grain weight (g), grain weight panicle-1 (g). In Binadhan-8, flag leaf alone or flag leaf with 2nd leaf and 2nd and 3rd leaves cutting showed profound reduction in grain number panicle-1 (35.14, 62.62, and 51.83%, respectively) and grain weight panicle-1 (29.18, 58.37 and 48.93%, respectively) while, cutting of 2nd leaf and 3rd leaf alone exert no significant impact compared to control. Number of unfilled grain increased with higher intensity of leaf cutting. In Terebaile, only flag leaf cut showed non-significant impact on grain number panicle-1 and grain weight panicle-1. Profound impact was observed by cutting flag leaf with 2nd leaf (55.47 and 48.98%, respectively) and flag leaf with 2nd and 3rd leaf (58.96 and 63.13%, respectively). Leaf clipping had non-significant effect on thousand grain weight of modern variety Binadhan-8 while, it had significant effect in TerebaileBangladesh Rice j. 2017, 21(1): 101-104